PTSD and anger: Evaluation of an indirect effect model in a civilian trauma sample. (September 2019) - Ripley, Adam J.; Clapp, Joshua D.; Wilkowski, Benjamin M.
Abstract: Background and objectives: Theoretical models propose that PTSD symptoms and subjective anger are indirectly associated through hostile attribution bias, physiological reactivity, and aggressive psycho-motor scripts (Chemtob, Novaco, Hamada, Gross, & Smith, 1997). Originally developed to account for symptoms observed in military personnel, proposed anger mechanisms have received limited attention in civilian populations. The current study looked to evaluate the generalizability of Chemtob et al.'s model in trauma-exposed university students ( N = 152). Methods: Trauma exposure and corresponding symptoms were assessed during an initial screening procedure. Hostile attributions and aggressive scripts were examined prior to a laboratory-based anger induction procedure. Physiological reactivity was monitored throughout the provocation task. Ratings of subjective anger and anger recovery were completed following the induction period. Relations of post-trauma symptoms with subjective anger through hypothesized anger processes were examined using bootstrapped estimates of indirect effects. Results: A significant indirect effect of PTSD severity on state-level anger was noted for hostile attribution bias ( ab = 0.020, 95% CI [0.002, 0.041]) and a marginal effect through aggressive inclinations ( ab = 0.015, 95% CI [-0.001, 0.039]). Data failed to provide evidence for physiological reactivity as an intervening variable. Trauma symptoms did not moderate anger recovery following the provocation task. Limitations: Induction of anger in a sub-clinical sample may limit tests of hypothesized effects and the generalizability of the present findings. Conclusions: Results indicate the proposed model may be applicable beyond combat trauma samples and suggest potential anger-related targets for PTSD treatment. Highlights: Study examines the generalizability of veteran model of PTSD and anger in civilians. Cognitive, arousal, and behavioral processes hypothesized as intervening variables. Data support indirect relation of PTSD and anger through hostile attribution biases. Additional evidence for indirect effect of aggressive psychomotor scripts. No indirect effect of cardiovascular reactivity in response to anger provocation.